2019
DOI: 10.1021/acscatal.8b04604
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing H2 Evolution and Promoting Selective CO2 Electroreduction to CO at Low Overpotentials by Alloying Au with Pd

Abstract: CO 2 electroreduction is a promising technology to produce chemicals and fuels from renewable resources. Polycrystalline and nanostructured metals have been tested extensively while less effort has been spent on understanding the performance of bimetallic alloys. In this work, we study compositionally variant, smooth Au−Pd thin film alloys to discard any morphological or mesoscopic effect on the electrocatalytic performance. We find that the onset potential of CO formation exhibits a strong dependence on the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 48 publications
1
71
0
Order By: Relevance
“…Currently, precious metals such as gold and palladium can effectively convert CO2 into CO or formate [19][20][21][22]; however, their high cost greatly limits their application in CO2RR. Indium and its alloys have already been proven to possess high catalytic properties for CO2RR to afford formate with a low cost [23][24][25][26][27][28][29]. However, the current density and selectivity of these catalysts are unsatisfactory at low overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, precious metals such as gold and palladium can effectively convert CO2 into CO or formate [19][20][21][22]; however, their high cost greatly limits their application in CO2RR. Indium and its alloys have already been proven to possess high catalytic properties for CO2RR to afford formate with a low cost [23][24][25][26][27][28][29]. However, the current density and selectivity of these catalysts are unsatisfactory at low overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Pd alloyed with Au has shown that the Au 75 Pd 25 alloy can increase the adsorbed CO surface coverage coupled with decreasing the vacant active sites for HER at lower applied potentials, leading to the favorable selectivity for CO production. 84 In this regard, the J CO on the Au-rich alloy was higher than that of Au for all applied potentials. Meanwhile, Au-Pd core-shell nanoparticles fabricated from an Au-Pd alloy core and an ultrathin Pd-rich shell were reported to activate CO 2 -to-CO conversion in another study ( Figure 6E).…”
Section: Noble Metallic Alloysmentioning
confidence: 82%
“…The addition of Cu to Pd has been shown to not only modulate the electronic structure and generate weaker binding of the CO to prevent CO poisoning of the Pd catalyst, but to change bond lengths of metallic atoms to decrease binding energy of hydrogen, which is beneficial for CO evolution. Lately, Pd alloyed with Au has shown that the Au 75 Pd 25 alloy can increase the adsorbed CO surface coverage coupled with decreasing the vacant active sites for HER at lower applied potentials, leading to the favorable selectivity for CO production . In this regard, the J CO on the Au‐rich alloy was higher than that of Au for all applied potentials.…”
Section: Metallic Alloysmentioning
confidence: 97%
“…[ 40,41 ] Alloying not only reduces the required amount of precious metals but also optimizes the geometric and electronic structure of metals sites [ 42 ] which is beneficial for improving activity and selectivity. [ 43–45 ] For example, for different Pd alloys with Ag, Cu, or Ni, etc. the alloying Pd with Ag can promote the electrochemical conversion of CO 2 to syngas due to the appropriate adsorption strength of intermediates on Pd–Ag alloy.…”
Section: Introductionmentioning
confidence: 99%